Analisis Manajemen Kredit Guna Menekan Terjadinya Kredit Bermasalah Dalam Pelaksanaan Program Kemitraan Pada Pt.Telekomunikasi Indonesia (Studi Kasus Di Community Development Sub Area Malang) - Leila Melati Mukhlishah; Djuma hir (Jurnal Ilmiah Mahasiswa FEB, 2012)
PT.Telekomunikasi Indonesia  is one of a BUMN Company. The purpose of the research    is  to  investigate  the  implementation of Partnership Program  is one of  the  corporate  social  responsibility  programs  which  is  managed  by  PT. Telekomunikasi Indonesia Sub Area Malang in helping small businesses. Funding for this program comes from  1-3% net profit.  PT.Telekomunikasi Indonesia form a  Community  Development  (CD)  to  manage  a  parternship  programe  in  their company. The  results of  this  study  indicate  that  credit management used at CD PT.Telekomunikasi  Indonesia  Sub  Area Malang  in managing  credits  are  credit planning,  organizing,  actuating  and  controlling.  In  other  hand,  the  cooperation also conducts 5C analysist  including character, capacity, capital, collateral and condition of economic to minimize and depress the risks of bad debt.  .Keywords: credit management, partnership programe, bad debt